31.E. Workshop: Food processing in the modern era: implication for public health. (30th September 2020) - ,; ,
Abstract: Current scientific evidence and reports from governmental organizations agree that healthy nutrition represents a key factor to prevent death and disability from major nutrition-related chronic diseases. For many years, the essential goal of healthy dietary recommendations included eating nutrient dense foods and limiting consumption of foods high in energy (sugar, starch and/or fat) to maintain a healthy weight. However, the scientific community abandoned the more simplistic approach of energy balance between calorie in and out, shifting into investigation of the whole diet quality as main determinant of health. With development of new technologies and globalization of the markets, the food availability improved worldwide, often in spite of (nutritional) quality and loss of local products production/consumption. As a result, there is an industry-supported wide spread of "non-traditional" foods, including processed foods characterized by various ingredients, added sugars, and additives that are highly influencing consumers' behaviors and, only recently, questioned for their role on general public health. This workshop aims to provide insights on consumption of ultra-processed foods up to the extreme processing of dietary supplements and their use and misuse, emphasizing on their potential impact on traditional dietary patterns. The objectives of the present workshop are the following: To provide a science-based definition of processed and ultra-processed foods; To explore current evidence of the association between ultra-processed foods and risk of chronic non-communicable diseases and mortality; To explore current evidence of the association between dietary supplements and human health; To discuss whether introduction of non-traditional foods may affect the relation between traditional dietary patterns and health. Given the novelty of the topic, it is crucial to summarize current evidence from lead experts on this field of research and sharing opinions with the audience in light of the presented results. The conclusions might have crucial implications for potential policy and research outcomes. Key messages: Uncontrolled consumption of ultra-processed foods and dietary supplements represent a potential threat for general public health. The inclusion of ultra-processed foods into traditional healthy dietary patterns may affect their efficacy in preventing chronic non-communicable diseases.